Feasibility of a Parenting Program to Prevent Substance Use Among Latino Youth: A Community-Based Participatory Research Study - Allen, Michele L. (2013)
PURPOSE: Family-skills training programs prevent adolescent substance use, but few exist for immigrant Latino families. This study assesses the feasibility of a family-skills training intervention developed using a community-based participatory research framework, and explores parental traditional values as a modifier of preliminary effects. DESIGN: One-group pretest-posttest. SETTING: Four Latino youth–serving sites (school, clinic, church, social-service agency). SUBJECTS: Immigrant Latino parents of adolescents aged 10 to 14 years (N = 83). INTERVENTION: Eight-session program in Spanish to improve parenting practices and parent-youth interpersonal relations designed with Latino parents and staff from collaborating organizations. MEASURES: Feasibility was assessed through retention, program appropriateness, and group interaction quality. Preliminary outcomes evaluated were (1) parenting self-efficacy, discipline, harsh parenting, monitoring, conflict, attachment, acceptance, and involvement, and (2) parent perception of adolescent internalizing, externalizing, and substance use behaviors. Covariates included sociodemographics and parental endorsement of traditional values. ANALYSIS: Feasibility outcomes were assessed with descriptive statistics. Paired t-tests measured changes in parenting outcomes. Adjusted multiple regression models were conducted for change in each outcome, and t-tests compared mean changes in outcomes between parents with high and low traditional values scores. RESULTS: Program appropriateness and group interaction scores were positive. Improvement was noted for eight parenting outcomes. Parents perceived that adolescent internalizing behaviors decreased. Parents with lower endorsement of traditional values showed greater pretest-posttest change in attachment, acceptance, and involvement. CONCLUSION: This intervention is feasible and may influence parenting contributors to adolescent substance use. (Am J Health Promot 2013;27[4]:240–244.)